Proyecto de factibilidad para la creación de una empresa procesadora de harina de sangre de pollo, y su comercialización en el cantòn Balsas, de la provincia de Eecl Oro - Romero Sànchez, Lisset Esperanza (2016)
For the present investigation the following general objective has been proposed: To carry out a FEASIBILITY PROJECT FOR THE CREATION OF A PROCESSING COMPANY OF CHICKEN BLOOD FLOUR AND THEIR MARKETING IN THE CANTÓN BALSAS, OF THE PROVINCE OF EL ORO, and specific objectives: To develop the Market research, to determine demand and supply. Determine a technical study where the size, location and engineering of the project are established. Prepare an administrative study to determine the structure and functions of the company. Carry out a financial economic study where the investment required by the project is determined, Prepare the financial evaluation according to the indicators VAN, TIR PRC, RBC, and Sensitivity Analysis of income and costs, in order to establish the profitability of the project. The research used methods and techniques that determine the process, these are: inductive method the same that was immersed in the collection of information related to the size of the sample, with general and real data of the population at the local level to determine the demand Potential, real, effective and unsatisfied demand, Inductive Method helped to perform the analysis of the information collected from the surveys, also allowed to determine the main aspects of the marketing plan, location, processes, organic structure and human resource functions , The descriptive method was used to describe the product according to the requirements that came from the information obtained in the study of the demand, the statistical method allowed to carry out the quantitative and qualitative analysis of the surveys, analytical method served to decompose the organizational structure into levels Hierarchical, the functions of the personnel; As well as to determine the required investment and costs in its different areas. The market study was carried out in the canton Balsas specifically to the producing companies of balance, with a sample of 30 companies; Tabulated surveys were analyzed to determine effective demand resulting in 41,759 sacks of 50 kilos of chicken blood meal for the first year. The Offer of 17,418.00 quintals of animal by-product meal and the Unsatisfied Demand of 24,341 quintals of balancing, which allowed to determine that the project can and should be executed, due to the results obtained in the analysis of the demand, supply and levels of Marketing of animal by-product meal. The unsatisfied demand reflects the potential market that exists in the canton Balsas to produce the chicken blood meal, with the following results: For the first year of the project's life the unsatisfied demand is: 24.341 bags of 50 kilos, Capacity Installed of the project determines that the company will be able to produce in the first year 18.230,00 bags of 50kilos, being 80% its production capacity, in addition it was determined that the location will be in the canton Balsas, Sitio La Esperanza. The production process demands the use of machines and equipment according to the need of production, which guarantees a product of high quality and at affordable prices according to those of the competition. Next, the project engineering was developed determining process diagrams, operational and management characteristics, technical requirements such as equipment, installations, furniture and appliances. Likewise, an administrative study was carried out determining itself as a Limited Liability Company Company. Ltda., With its respective functional organizational structure at the hierarchical levels: Legislative, Executive, Adviser, Auxiliary Level of Support, Operational Level, as well as function manuals and organizational charts; Which were used to implement a good organization, since the following personnel will be employed: Manager, Secretary, Contadora who will be part of the Administrative staff, in the operational personnel is distributed as follows: a Production Manager, 4 operators and finally You will find the sales staff with a marketing chief, a salesperson and a cashier. The project reaches an investment of 211,238.38 dollars and will be financed with a contribution from the partners of 52.66% of the total investment corresponding to $ 111.238,38 dollars and a loan that will maintain in the Pichincha Bank will constitute the 47,34% corresponding to $ 100.00.00 dollars to 5 years term with an interest rate of 11.23% per annum. The financial evaluation presents the following results: According to the NPV of the present project gives a positive value of $ 212,721.41 dollars, indicating that the project or investment is feasible. For the present project the IRR is 46.32%; Being this satisfactory value to realize the project, the time that would be required to recover the original investment would be 3 years, 1 months and 6 days, for the present project, the values of sensitivity are smaller than one, therefore, they do not affect the Project changes in costs can be increased 28,07% and revenues decreased by 17.50%, respectively, ie the project is not sensitive to these changes. Among the most significant conclusions and recommendations is that the market study carried out in the canton Balsas determines that the project can and must be executed due to the results obtained in the analysis of supply and demand. It has been demonstrated that there is a considerable unsatisfied demand for the product to be manufactured which, with the implementation of the company will cover 80% of its demand for unsatisfied.